Maintenance safety in food factory / Mohd Aizuddin Ibrahim - Ibrahim, Mohd Aizuddin (Faculty of Architecture, Planning and Surveying, 2009)
Factory is a place to produce a product such as vehicle, cloth, food, electrical item, etc. Apart from products manufacturing to daily use, it is also one of the dangerous places because it contains heavy machinery which can cause serious injuries. Factory is the place where human work together with machinery. As a worker in food factory, priority to safety is very importance. The safety level in food factory is similar to other factories where it should be given priority because accident can happen anywhere regardless of time and place. It is also to ensure that all of the workers are safe while working in factory area. To identify safety level, research has been done at Nestle Manufacturing Sdn Bhd, Batu Tiga, Shah Alam, Selangor. The effectiveness of maintenance program was identified and analyzed to ensure the level of safety. The findings were that, all workers had their right when working in the factory because the safety level in the factory is excellent. Besides that, they also had right which is can work in safe environment.